Factors influencing residents attitude towards tourism development on the remote island of Socotra, Yemen - Al-Gahuri, Hussein Abdulqader (2014)
Tourism has been considered as a strategy to generate economic benefits and to develop the local community, economically and socially. However, tourism requires a lot of participation and support by the local community to be sustained. Getting participation and acceptance from local community is perhaps the greatest challenge to the national government. This challenge seems apparent in Yemen which is viewed as one of the most conservative Islamic countries, where Islamic values and culture, and the tribal conventions come in contradiction to the Western tourists' practices. This study investigates the influence of residents' attitudes toward tourism development in a conservative community of Socotra Island in Yemen by determining the influence of Islamic values on the residents' attitudes toward tourism development, investigating the influence of socio-demographic characteristics on the residents' attitudes on tourism development, assessing the influence of personal benefits from tourism on the residents' attitudes toward tourism development, and examining the influence of knowledge about tourism on the residents attitudes on tourism development. Data was collected using quantitative and qualitative methods. A total of 359 usable questionnaire responses were collected and analyzed by using a variety of statistical techniques. In addition, 20 interviews with local leaders were conducted. The result shows a negative relationship between the residents' Islamic values and their attitudes toward tourism development in a conservative community of Socotra Island. The findings also indicate that social demographic characteristics, personal benefits from tourism, and knowledge about tourism have positive relationships with residents' attitudes toward tourism development. This study extends the literature on residents' attitudes toward tourism by highlighting Yemeni Islamic values as a new variable in understanding community perceptions and attitudes toward tourism. In addition, it provides important managerial and methodological contributions to the literature, particularly with regards to the understanding of the residents' attitudes toward tourism, specifically in a conservative community such as Yemeni community. Recommendations are given on how government and policy makers in Yemen can make contributions to develop tourism. Finally, the study suggests further studies including investigating other factors that may influence the residents' opinions and perceptions on tourism.